Język serbsko-chorwacki jako immanentny determinant jugoslawizmu - Gucka, Agnieszka (Slavia Occidentalis, 2011)
The article “Język serbsko-chorwacki jako immanentny determinant jugoslawizmu” (The Serbo-Croatian Language as an Immanent Determinant of Yugoslavism) outlines the way in which the Balkan languages, especially the Serbian and the Croatian, converge and diverge. The author of the article indicates the events that led to their unification (for example, the attempts from 1850 to choose the most popular dialect) and also the situations which provoked the struggle for the separation of the languages. Furthermore, the author demonstrates that in the Balkans the struggle for the language was, and still is, an element of political strife (e.g., the attempts to introduce a general, official Yugoslavian language, then called the Serbo-Croatian-Slovenian language). The emphasis in the article is placed on the condition of the Croatian language after the disintegration of Yugoslavia. The author also discusses the relevant decrees, agreements, declarations and the activities of special administrative organs (such as the Croatian National Language Bureau) and ponders over the future of the Balkan languages.